Karakteristik dermatitis kontak akibat kerja pada pengrajin patung di Desa Mas, Ubud tahun 2016 - Ni Putu Melda Dharmahayu; Nyoman Suryawati (E-Jurnal Medika Udayana, 2018)
Occupational contact dermatitis is an abnormal condition caused by substance or process that correlated with work. One of the occupations that have the risk in contact dermatitis is artisans sculpture. The aimed of this study is to describe the characteristic of occupational contact dermatitis in artisans sculpture at village of Mas, Ubud, Gianyar in 2016. This study is a kind of descriptive study with cross sectional approach. Total sample of artisans sculpture with contact dermatitis or history of contact dermatitis as many as 48 people collect through interviews with the questionnaire. The result of this research obtained the highest range 41-50 years old (43.8%), sex dominant male (54.2%), most respondents don’t have history of atopic in themselves (73%) or family (79.2%). The common symptom is dry skin (87.5%), most common is palms (91.7%), the most common duration of contact is >7 hours/ day (58,7%), frequency of exposure is mostly >8 times/day, the chemical substance that most common has contact with respondents is soap (87.5%), working period is mostly >4 years, and most of the artisans sculpture have history of skin diseases before (54%). High incident of occupational contact dermatitis on artisans sculpture at village of Mas, Ubud because of the lack knowledge about the diseases that related to their work and lack of use of personal protective equipment (PPE). So we need preventive action such as awareness of using personal protective equipment during work. We need continuation of this research to gain more comprehensive data. Keywords: occupational contact dermatitis, artisans sculpture, characteristics